2014
DOI: 10.1364/oe.22.016731
|View full text |Cite
|
Sign up to set email alerts
|

ZnO ultraviolet random laser diode on metal copper substrate

Abstract: Direct fabrication of light emitting devices on metal substrates is highly desirable due to their advantages of high thermal conductivity and light reflection. In this work, we demonstrated a feasibility of directly fabricating ZnO-based ultraviolet laser diodes on metal substrates. By introducing an anti-oxidation buffer layer, Au/MgO/ZnO metal-insulator-semiconductor heterojunction devices are successfully fabricated on the copper substrate. Electrically pumped ultraviolet random lasing was achieved from ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Undoped ZnO typically usually acts as an n-type semiconductor, with a hexagonal wurtzite structure and lattice constants a=3.24 Å and c=5.20 Å [2]; it has attracted substantial considerable attention owing to its wide range of applications in, for example, light-emitting diodes [3], varistors [4], gas sensors [5], laser diodes [6], SAW devices and field emission (FE) devices [7][8]. ZnO nanostructures have been extensively investigated owing to their remarkable physical and chemical properties that can be exploited in various electronic devices and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Undoped ZnO typically usually acts as an n-type semiconductor, with a hexagonal wurtzite structure and lattice constants a=3.24 Å and c=5.20 Å [2]; it has attracted substantial considerable attention owing to its wide range of applications in, for example, light-emitting diodes [3], varistors [4], gas sensors [5], laser diodes [6], SAW devices and field emission (FE) devices [7][8]. ZnO nanostructures have been extensively investigated owing to their remarkable physical and chemical properties that can be exploited in various electronic devices and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their application in devices, such as field-effect transistors, 19,20 ultraviolet (UV) photosensors, 21,22 UV light-emitting diodes, 23 glucose sensors, 24,25 varistors, 26 gas sensors, 27 laser diodes, 28 surface acoustic wave (SAW) devices, 29 solar cells, 30,31 memory devices, 32,33 and field emission (FE) devices, 34 is promising. In recent years, FE devices have gained widespread attention for their application in flat-panel displays and other electronic devices, such as microwave amplifiers, high-brightness electron-source X-ray tubes, cathode-ray tube monitors, and electron microscopes.…”
mentioning
confidence: 99%
“…So far, as gain materials, many studies on UV ZnO lasers have also been reported in various micro-/nano-cavity structures, such as random structures, [1][2][3][4][5][6][7][8][9][10][11][12][13] Fabry-Perot cavities, [14][15][16][17] whispering-gallery-mode resonators. [18][19][20][21] Although, in most of these ZnO lasers, the gain from electron-hole plasma (EHP) recombination under high excitation intensity condition has typically been reported as the origin of the stimulated emission (photon lasing), 12,13 the lasing originated by excitonic recombination, so-called polariton/exciton lasers, has also been demonstrated in well-designed cavity structures at room temperature.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…In particular, because ZnO has the above-mentioned advantages and high gain, there are numerous studies on RLs so far. [1][2][3][4][5][6][7][8][9][10][11][12][13] In typical random structures, because localized modes are spontaneously formed and its modal control is difficult due to the multiple light scattering, the lasing peak wavelengths depend mainly on the property of gain materials and their thresholds are determined by the mean scattering property of the structure. Furthermore, the features of the RL (e.g., multimode lasing and high thresholds) make it difficult to realize strong interactions between cavity modes and gain materials and observe cavity-related phenomena, [21][22][23][24] like observed in well-designed resonators, as mentioned above.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%